PENGARUH VARIASI SUHU PENYIMPANAN TERHADAP VITALITAS SPERMA - I Wayan Merta (Meditory : The Journal of Medical Laboratory, 2017)
Background. Sperm is very sensitive to changes in temperature, this can cause changing the characteristics of spermatozoa. To perform sperm analysis it is necessary to determine the optimal storage temperature to keep the characteristic of sperm samples remain representative.Objective. The purpose of this study to determine the effect of variation in storage temperature on sperm vitality, in order to determine the optimal storage temperature of sperm samples when delay of examination.Methods. In this study we used microscopic method with supravitalstainting using 0,5% eosin staint. Dead spermatozoa will be stained by eosin and live spermatozoa will not be stained by eosin.The study was conducted on 8 subject of the Department of Health Analyst Poltekkes Denpasar that selected by randomly simpling with One Group pretest-posttest design. The measured variable is the value of sperm vitality before and after treatment.Results : Analysis with T-Paired test showed significant difference before and after treatment (p 0,05) before treatment 84,687% ± 3,796, to 78.725% ± 3.809 at 4oC, at temperature 25oC is 82,7875 % ± 3,588, and at 37°C is 70% ± 4,152. Conclusion. From the results of research that has been done, it can be concluded that the decrease in sperm vitality is obtained at least 25oC storage temperature for 1 hour and the most decrease obtained at storage at 37oC for 1 hour. Keywords: Sperm vitality, spermatozoa